Case Report: Fenestration embedded in large vessel occlusion at non-branching site: A catastrophic trap for mechanical thrombectomy - Zhang, Xiaoxi; Hua, Weilong; Zhang, Lei; Zhang, Yongxin; Zhang, Yongwei; Liu, Jianmin; Yang, Pengfei; Xu, Xiaolong; Li, Zifu (Frontiers in Surgery, 2022)
Fenestrations are rare anatomical variants characterized by division of an artery into two channels which join distally to form a single lumen. We here present two acute ischemic stroke patients with occlusion in an arterial segment with fenestration. Both occlusion sites were located at the non-branching site: one in the mid-basilar trunk and one middle cerebral artery trunk. Successful reperfusion was achieved in both patients, but angioplasty was avoided during thrombectomy procedure. The two cases establish that fenestration may be embedded in non-branching site occlusion. Surgeons should take this abnormality into account to prevent angioplasty from causing vessel rupture in the setting of fenestration.